2010
DOI: 10.1117/12.860463
|View full text |Cite
|
Sign up to set email alerts
|

Influence of point defects on the performance of InVO 4 photoanodes

Abstract: The properties of thin film InVO 4 photoanodes for water splitting have been studied. Compact films of InVO 4 were prepared by spray pyrolysis and are found to be stable between pH 3 -11. Although the indirect bandgap is 3.2 eV, a modest amount of visible light absorption is observed. The origin of this absorption is attributed to the presence of deep donor states at ~0.7 eV below the conduction band. Shallow donors are absent in this material, in contrast to what is normally observed for metal oxides. The dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…An insignificant deviation from stoichiometry of In to V can also give rise to appreciable concentration of oxygen vacancies in the lattice. The authors have confirmed the presence of such oxygen vacancies by photoluminescence studies . In addition, the structure of InVO 4 can be explained as distorted cubic close‐packed oxygen lattice with partially occupied octahedral and tetrahedral sites.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…An insignificant deviation from stoichiometry of In to V can also give rise to appreciable concentration of oxygen vacancies in the lattice. The authors have confirmed the presence of such oxygen vacancies by photoluminescence studies . In addition, the structure of InVO 4 can be explained as distorted cubic close‐packed oxygen lattice with partially occupied octahedral and tetrahedral sites.…”
Section: Resultsmentioning
confidence: 74%
“…However, the O–V–O angles in all of them remain close to the normal tetrahedral angles. Such distortions often destabilize the lattice and thus the structure has a tendency for polymorphic transformation under temperature or pressure, as well as to form significant amounts of intrinsic point defects in the lattice . To understand further on these aspects and their correlation with the electrical properties, in situ high‐temperature XRD and high‐temperature ac ‐ impedance studies were carried out and results are explained subsequently.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations